(untitled) (Journal of the College of Basic Education, 2022)
The significance of the shift on change can be used to monitor models of response structuresaesthetic. through which a number of poets tried to perpetuate an image of excellenceTheir peculiarity is unique, because the transformation in the essence means "the occurrence of a new substantial imageThe old man went to the Golkhoubitel district of Aiha for poems to germinate a kind of independence in expressionThrough it, people try to achieve their own model and independent voice, but do they not?Does that include the complete poetic fetching? The answer to that does not need much research to provelack of access; The element of transformation remained within the poems mostly subject toThe Arab poetic heritage and its purposes